2012
DOI: 10.1021/jp3089098
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Vibrational Relaxation Dynamics of a Rhenium Bipyridyl CO2–Reduction Catalyst at a Au Electrode Surface Probed by Time-Resolved Vibrational Sum Frequency Generation Spectroscopy

Abstract: The vibrational relaxation dynamics of a rhenium bipyridyl CO 2 -reduction catalyst chemisorbed to a model Au electrode surface have been investigated using broadband time-resolved vibrational sum frequency generation (VSFG) spectroscopy. IR pump-VSFG probe spectra indicate a biexponential decay of the excited vibrational population, consisting of an ultrafast initial relaxation followed by complete recovery of the ground vibrational state within tens of picoseconds. The ultrafast decay is assigned to rapid po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 49 publications
(67 reference statements)
6
50
0
1
Order By: Relevance
“…[40][41][42][43][58][59][60][61] Therefore, the orientation analysis presented here can be directly applied to these spectral regimes. In addition, since only the diagonal cuts of HD 2D VSFG are analyzed to obtain the orientation heterogeneity, in principle, the same method can be applied to IR pump-SFG probe experiments 38 when there is no coupling between vibrational modes. This extension enables the orientation heterogeneity measurement by a more established technique than HD 2D VSFG.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43][58][59][60][61] Therefore, the orientation analysis presented here can be directly applied to these spectral regimes. In addition, since only the diagonal cuts of HD 2D VSFG are analyzed to obtain the orientation heterogeneity, in principle, the same method can be applied to IR pump-SFG probe experiments 38 when there is no coupling between vibrational modes. This extension enables the orientation heterogeneity measurement by a more established technique than HD 2D VSFG.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is more difficult to capture the characteristic signal changes of semiconductor QDs in the catalytic process, which makes the current research on the catalytic mechanism of QDs based systems lagging behind. In the future, more advanced and sophisticated characterization methods need to be applied, such as ultrafast spectroscopy, surface sensitive nonlinear spectroscopy, in situ infrared spectroscopy, time‐resolved X‐ray absorption spectroscopy (XAS) and so on . These technologies can not only provide us with more information about the structure and composition of materials, but also reflect the dynamic information of charge carriers.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37] TR-SFG probes have been employed to study the vibrational dynamics of rhenium catalysts tethered to gold surfaces through an alkane thiol spacer. 38 The negligible substrate effect was attributed to the spacer that hindered energy transfer from the catalyst to the gold surface. 38 TR-SFG studies of these catalysts adsorbed on TiO2 single crystals revealed that the relaxation time is dependent on the crystallographic facets.…”
Section: Toc Graphicmentioning
confidence: 99%
“…38,40,47,53 The fast component with smaller amplitude can be attributed to the rapid population equilibration between different carbonyl stretching modes, followed by slow recovery of the ground state in tens of picoseconds. 38,40 cm -1 are attributed to GSB/SE and ESA of the A'(1) mode, respectively. Similarly, the signals at lower frequency are attributed to GSB/SE and ESA of the A'' and A'(2) modes, respectively.…”
Section: Toc Graphicmentioning
confidence: 99%
See 1 more Smart Citation